An Analysis of Word Formation Process in Written Descriptive Text by the Eleventh Graders of SMA Negeri 1 Candimulyo in the School Year of 2017/2018 - Maya Purwaningrum (Faculty of Education and Teachers Training, 2019)
Writing is considered difficult skill to be learned. It needs the ability to express ideas that should be stated clearly, efficiently in a written form. In learning writing, the students will have a chance to do that through descriptive text. They have to give much attention on words choices to build the text. The students usually focus on the vocabulary because it will take time to analyze the process in the creation of words. Word formation process is important to gives knowledge about the rules on how to create a new word. The research’s aims are to describe the types of word formation process found in descriptive text written by the eleventh graders of SMAN 1 Candimulyo and to find the type of word formation process that are mostly used in descriptive text written by the eleventh graders of SMAN 1 Candimulyo. The subject is the eleventh graders’ descriptive text compositions of class XI MIPA 1 of SMAN 1 Candimulyo in the school year of 2017/2018. The results revealed, the total number of word formation process are 151 words, contributed in 8 types out of 11. Initialization, acronym are counted separately. They are 68 inflections or 45.03%, 46 derivations or 30.46%, 14 compoundings or 9.27%, 8 initializations or 5.30%, 6 coinages or 3.98%, 4 acronyms or 2.65%, 4 multiple processes or 2.65%, and 1 clipping or 0.66%. The most dominant type is inflections, 45.03%. The lowest is clipping in which there is 1 clipping out of 151 words or 0.66%.